Levels and determinants of youth political participation - Kirbiš, Andrej (Studia Historica Slovenica, 2018)
The main purpose of our study was 1) to analyse previously unexamined regional inequalities in four dimensions of political participation among Slovenian youth (self-reported voter turnout, non-electoral conventional participation, protest participation and civic participation); 2) to examine macro-determinants of regional inequalities in political participation; and 3) to examine regional variation in individual-level determinants of political participation. We found several substantial regional inequalities in youth political participation, although the extent of inequalities differed depending on examined participation dimension. Regional inequalities exist particularly in voter turnout and civic participation, while at the same time, regions that score higher on one dimension in some cases score lower on other dimensions.
Keywords: mladina; neenakost; politična angažiranost; regije; severovzhodna Slovenija; Slovenija